If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-8=f/5
We simplify the equation to the form, which is simple to understand
-8=f/5
Simplifying:
-8=0.2f
We move all terms containing f to the left and all other terms to the right.
-0.2f=+8
We simplify left and right side of the equation.
-0.2f=+8
We divide both sides of the equation by -00.2 to get f.
f=-40
| 38-4x=6(x+8) | | -3=k+3 | | (2t^2+7t-6)-(3t^2-11t-9)=0 | | 23=3+37t-16t^2 | | -8=2+3m-1 | | 5(x+3)-(2x-1)=3 | | 0.35x+.05(12-x)=.10(-48) | | -8=2+9m-1 | | 4x-9x=39 | | d-4.9=18.8 | | -[7x-(3x+10)]=-3-[4(2x-4)-2x] | | 3(3n+3)=9(6n+5)8 | | 6(x-5)=-48 | | 0.5x-0.3(2-x)=4.6 | | -4=a+6 | | 9x^2+3x-3xy-y=0 | | 5x^2-2x^2+9x^2+x^2=0 | | .01x+.10x+.25(35-2x)=4.07 | | 5+3x+2x+7=2 | | 4p^3+36p=0 | | 42-x=19 | | c-4=13.7 | | 6x*x+7x-20=0 | | n-6=-10 | | 0=x^2-25x+144 | | 9(5+x)=15(10+x) | | 4x-(9-3x)=18x-1 | | w=4+8 | | 15-j+5j+2=-14 | | p=4+8 | | -4(x+4)=5-(-4) | | 2(-18)+3=3(-18)+7 |